Correlation Of Serum 25-Hydroxyvitamin D Levels With Glycemic Control In Type 2 Diabetes Mellitus Patients - Putri, Septia Harma; Aprilia, Dinda; Decroli, Eva (TALENTA Publisher, Universitas Sumatera Utara, 2025)
ABSTRACT Background: Type 2 diabetes mellitus (T2DM) is caused by reduced insulin sensitivity, which can lead to insulin shortage. Several recent investigations have found that vitamin D is connected with insulin secretion and sensitivity. Vitamin D insufficiency is linked to poor glucose regulation. Aim: To determine the correlation between serum 25-hydroxyvitamin D levels and glycemic control in Type 2 DM patients. Method: T2DM patients' serum levels of 25-Hydroxyvitamin D, Fasting Blood Glucose (FBG), 2-hours postprandial blood glucose (2-h PBG), and HbA1c were examined in this cross-sectional analytical observational study. Statistical analysis was also performed. Result: From 49 samples included, the number of male subjects was almost the same as female, mean age was 58 years. There was a decrease in serum 25-Hydroxyvitamin D levels with a median of 27.87 ng/ml (12,626 -94,367). Glycemic control was found to be poor, the median of FBG levels was 134 mg/dl (61-339), 2-h PBG levels was 208 mg/dl (93-488) and HbA1c levels was 7.5% (5.6-12.8). Analysis using Spearman correlation between serum 25-Hydroxyvitamin D levels with levels of FBG, 2-h PBG and HbA1c showed values of r = -0.538 and p = 0.000, r = -0.354 and p 0.013, r = -0.501 and p 0.000. Conclusion: There was a statistically significant negative correlation between serum 25-Hydroxyvitamin D levels and levels of FBP, 2h-PBG and HbA1c in T2DM patients. Keywords: 25-Hydroxyvitamin D serum, glycemic control, fasting blood glucose, two-hour postprandial blood glucose, HbA1c.